2018
DOI: 10.1002/joc.5443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the subtropical westerly jet and its effects on the projected summer rainfall over central Asia using multi‐CMIP5 models

Abstract: The first two leading EOF modes of the summer zonal wind anomaly at 200 hPa over 25–55°N, 40–80°E for 1961–2004 in (a) and (b). The normalized principal component (PC) corresponding to the leading modes of EOF1 (c) and EOF2 (d).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…Some studies attempted to explore this question in terms of atmospheric circulation anomalies. Zhao et al (2018) suggested that variation in the axis of the western Asian (40°-80°E) subtropical westerly jet plays an important role in changes in summer rainfall over CA. Water vapor over the tropical Indian Ocean (IO) is closely related to rainfall over CA (Mason and Goddard 2001;Oliver et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies attempted to explore this question in terms of atmospheric circulation anomalies. Zhao et al (2018) suggested that variation in the axis of the western Asian (40°-80°E) subtropical westerly jet plays an important role in changes in summer rainfall over CA. Water vapor over the tropical Indian Ocean (IO) is closely related to rainfall over CA (Mason and Goddard 2001;Oliver et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Endris et al [37] carried out a study in Africa and projected rainfall from 2070-2099 using General Climate Model (GCMs) on Representative Concentration Pathway 8.5 (RCP 8.5) was first divided in 3 seasons which were; Jun until September (JJS), March until May (MAM) and October until December (OND). From the analysis, OND rainfall events to be increase while MAM and OND to be decreasing on most of Africa regions.…”
Section: Statistical Downscalingmentioning
confidence: 99%
“…Several studies have evaluated the ability of models to represent the observed EAJ climatology, location, intensity, and interannual variability. It has been reported that some individual models can generally capture the spatial structure of climatological summer EAJ (Song and Zhou 2013;Du, Bao, and Xie 2017;Zhao et al 2018) and its interannual relationship to the EASR (Lu and Fu 2010). However, by analyzing the output of the Community Climate Model Version 3, Zhang and Guo (2005) found a large bias in the simulated intensity and location of the EAJ, which caused unreasonable maximum precipitation to be simulated over East Asia.…”
Section: Introductionmentioning
confidence: 99%